2016
DOI: 10.3758/s13423-016-1079-5
|View full text |Cite
|
Sign up to set email alerts
|

Eliciting explanations: Constraints on when self-explanation aids learning

Abstract: Generating explanations for oneself in an attempt to make sense of new information (i.e., self-explanation) is often a powerful learning technique. Despite its general effectiveness, in a growing number of studies, prompting for selfexplanation improved some aspects of learning, but reduced learning of other aspects. Drawing on this recent research, as well as on research comparing self-explanation under different conditions, we propose four constraints on the effectiveness of self-explanation. First, self-exp… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
40
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 53 publications
(41 citation statements)
references
References 72 publications
(122 reference statements)
1
40
0
Order By: Relevance
“…This—partly—aligns with findings of studies investigating the effects of pairing medium ability group members with either high or low ability members, namely that the more knowledgeable member (high and medium ability, respectively) gains the most from the collaborative endeavour (Denessen, Veenman, Dobbelsteen, & van Schilt, 2008). A plausible explanation for these results could be that high ability members benefit from explaining things to less knowledgeable group members, which is often referred to as the self‐explanation effect (Hausmann & VanLehn, 2010; Rittle‐Johnson & Loehr, 2017). By contrast, other studies found that high ability group members benefit most from a collaborative endeavour with other high ability group members.…”
Section: Group Members' Engagement and Prior Knowledge: Mine Ours Anmentioning
confidence: 99%
“…This—partly—aligns with findings of studies investigating the effects of pairing medium ability group members with either high or low ability members, namely that the more knowledgeable member (high and medium ability, respectively) gains the most from the collaborative endeavour (Denessen, Veenman, Dobbelsteen, & van Schilt, 2008). A plausible explanation for these results could be that high ability members benefit from explaining things to less knowledgeable group members, which is often referred to as the self‐explanation effect (Hausmann & VanLehn, 2010; Rittle‐Johnson & Loehr, 2017). By contrast, other studies found that high ability group members benefit most from a collaborative endeavour with other high ability group members.…”
Section: Group Members' Engagement and Prior Knowledge: Mine Ours Anmentioning
confidence: 99%
“…Self-explaining involves the generation of explanations of a problem-solution to oneself rather than simply answering tasks passively. Indeed selfexplaining has been shown to foster knowledge acquisition and to promote transfer in a variety of other domains (Lombrozo, 2006;Dunlosky et al, 2013;Wylie and Chi, 2014;Fiorella and Mayer, 2016;Rittle-Johnson and Loehr, 2017; for reviews see Bisra et al, 2018), but the effectivity in CT-instruction is not yet clear. Self-explaining is assumed to lead to the construction of meaningful knowledge structures (i.e., mindware), by investing effort in identifying knowledge gaps or faulty mental models and connecting new information to prior knowledge (e.g., Chi, 2000;Atkinson et al, 2003;Fiorella and Mayer, 2016), and seems especially effective in domains guided by general underlying principles (Rittle-Johnson and Loehr, 2017).…”
Section: Introductionmentioning
confidence: 99%
“…As noted earlier, two studies (Rittle-Johnson, 2006; Rittle-Johnson & Loehr, 2016) reveal the limitations of elicited self-explanation as an instructional technique in which students are prompted but not explicitly taught to generate self-explanations. However, a randomized controlled trial conducted by Fuchs and colleagues (2016) indicates that instructional time devoted to high-quality explanations is a productive instructional activity, as long as an explicit form of self-explaining instruction is used.…”
Section: Discussionmentioning
confidence: 94%
“…Rittle-Johnson (2006) demonstrated that self-explanation can help students develop conceptual understanding and transfer mathematical skills to unfamiliar problems in third through fifth grade, although effects were not stronger than other instructional conditions. Rittle-Johnson’s recent work indicates that while self-explanation is generally effective for promoting learning in some domains, its use limits learning in other areas: inhibiting the acquisition of certain types of knowledge even as it promotes the acquisition of others (Rittle-Johnson & Loehr, 2016). McEldoon, Durkin, and Rittle-Johnson (2013) established the benefits of explanation in promoting conceptual and procedural understanding for elementary students with lower levels of mathematics understanding, but as with Rittle-Johnson, student outcomes were not stronger than with other forms of instruction.…”
Section: Self-explanation As An Instructional Toolmentioning
confidence: 99%